2019
DOI: 10.1101/857003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of leadered and leaderless gene structures on translation efficiency, transcript stability, and predicted transcription rates inMycobacterium smegmatis

Abstract: 16Regulation of gene expression is critical for the pathogen Mycobacterium tuberculosis to tolerate 17 stressors encountered during infection, and for non-pathogenic mycobacteria such as 18Mycobacterium smegmatis to survive stressors encountered in the environment. Unlike better 19 studied models, mycobacteria express ~14% of their genes as leaderless transcripts. However, the 20 impacts of leaderless transcript structures on mRNA half-life and translation efficiency in 21 mycobacteria have not been directly t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…We have previously demonstrated that a substantial subset of M. tuberculosis mRNAs is transcribed as leaderless transcripts that lack a 5'UTR and associated ribosomal recognition signals, but quantification of translation rates for this pathogen at a genome-wide level was lacking. From the data presented here, we were able to quantify similar reliable rates of translation for leaderless Spearman's r value mRNAs (436 out of 2,598; 17%) and for Shine-Dalgarno mRNAs (486 out of 2,598; 19%); thereby corroborating that M. tuberculosis is able to efficiently initiate global translation of leaderless transcripts during exponential growth even in the absence of a Shine-Dalgarno sequence (Shell et al, 2015;Nguyen et al, 2020). Translation efficiencies (TEs) were calculated by dividing the RPKM of the translatome by the RPKM of the transcriptome and revealed significantly higher median efficiency levels for Shine-Dalgarno genes (Mann-Whitney test, P = 0.0195; Figure 2A), confirming previous observations between these genes and higher levels of expression (Ma et al, 2002).…”
Section: Broad Leaderless Translation During Exponential Growthsupporting
confidence: 74%
See 2 more Smart Citations
“…We have previously demonstrated that a substantial subset of M. tuberculosis mRNAs is transcribed as leaderless transcripts that lack a 5'UTR and associated ribosomal recognition signals, but quantification of translation rates for this pathogen at a genome-wide level was lacking. From the data presented here, we were able to quantify similar reliable rates of translation for leaderless Spearman's r value mRNAs (436 out of 2,598; 17%) and for Shine-Dalgarno mRNAs (486 out of 2,598; 19%); thereby corroborating that M. tuberculosis is able to efficiently initiate global translation of leaderless transcripts during exponential growth even in the absence of a Shine-Dalgarno sequence (Shell et al, 2015;Nguyen et al, 2020). Translation efficiencies (TEs) were calculated by dividing the RPKM of the translatome by the RPKM of the transcriptome and revealed significantly higher median efficiency levels for Shine-Dalgarno genes (Mann-Whitney test, P = 0.0195; Figure 2A), confirming previous observations between these genes and higher levels of expression (Ma et al, 2002).…”
Section: Broad Leaderless Translation During Exponential Growthsupporting
confidence: 74%
“…In particular there is increasing evidence to show that distinct populations of ribosomes preferentially translate mRNAs with certain features (Xue and Barna, 2012;Byrgazov et al, 2013;Shi et al, 2017;). Untranslated regions (UTRs) of mRNAs can influence the stability and translational efficiency of the transcript either by providing binding sites for regulatory proteins or RNAs, adopting secondary structures such as internal ribosome entry sites or by repressing translation (Hughes, 2006;Morris and Geballe, 2000;Nguyen et al, 2020). Furthermore, short open reading frames (ORFs) within 5' UTRs may inhibit translation by occluding the start codon or may themselves be translated (Ruan et al, 1994;Cao and Geballe, 1995;Werner et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation